Coexistence of carcinoma cheek with tuberculosis: a rarity - Mishra, Ashwini Kumar; Kant, Surya; Verma, Laxmi; Nagaraju, Karthik; Upadhyay, Noopur; Singh, Anubhuti; Kumar, Ankit (International Journal of Research in Medical Sciences, 2017)
Coexistence of tuberculosis and cheek malignancy is a rare phenomenon and it has never been reported to the best of our knowledge. Here, we present a case of carcinoma cheek with tuberculosis in a 50 year old male patient who was successfully managed by multimodality approach by combining anti-tubercular therapy with chemotherapy and radiotherapy.